Tamizaje fitoquímico y efecto antifúngico in vitro del extracto fluido de las hojas de Phthirusa robusta Rusby (suelda con suelda) frente a Candida albicans - Llontop López, Nuria Gabriela (2018)
The objective of this research work was to carry out phytochemical screening and to evaluate the in vitro effect of Phthirusa robusta Rusby leaf extract (soldered solder) against Candida albicans. The liquid extract was obtained through the fractional percolation of 1 kg of leaves of Phthirusa robusta Rusby (welded with solder) from the city of Tarapoto, province of San Martín, San Martín region. A sequence of the fluid extract was carried out and preliminary phytochemical screening was carried out using the Martínez and Cuéllar method. The fluid extract was divided into chloroform, ethanolic and aqueous extracts, in which the different phytochemical tests were carried out. Finally, the antifungal effect of the Phthirusa robusta Rusby fluid extract "solder solder" was determined by the disk diffusion method - Kirby & Bauer at concentrations of 0.1 g / ml, 0.2 g / ml, 0.3 g / ml against Candida albicans. In the chloroform fraction of leaves of Phthirusa robusta Rusby, triterpenes-steroids, fatty compounds, were qualitatively identified. In the ethanolic fraction of leaves of Phthirusa robusta Rusby, reducing sugars, triterpene-steroids, phenols, tannins, quinones, cardenolides, alkaloids, amino acids, flavonoids and anthocyanidin were qualitatively identified, and in the leaf fraction of Phthirusa robusta Rusby, alkaloids were qualitatively identified , flavonoids, reducing sugars, phenols / tannins. The fluid extract of leaves of Phthirusa robusta Rusby "welds with solder" presented a content of 0.1 g / ml, 0.2 g / ml and 0.3 g / ml of halos of inhibition, with average values of 8.69mm ± 2.1, 11.38 mm ± 0.5 , 13.06 mm ± 1.53 respectively. The fluid extract, with statistically significant differences (p <0.05) at concentrations of 0.2 and 0.3 g / ml, presenting antifungal effect against Candida albicans